Profile of MTs Students' Spatial Reasoning in Solving Contextual Problems Based on Mathematical Ability - Rizki Kurniawan Rangkuti; Dwi Juniati (CV. AFDIFAL MAJU BERKAH, 2022)
Spatial reasoning as an important component in students' mathematical thinking and problem solving. How do students think spatially, how is the flow in solving contextual problems, this is spatial reasoning. Spatial reasoning consists of three characteristics, namely perceiving, visual-spatial and transforming. This research is included in descriptive qualitative which aims to describe the spatial reasoning of MTs students in imagining and explaining parts of objects, mentioning and describing parts of objects and changing the shape of objects from the problems given. The subjects in this study were three students from class VIII of MTs Negeri 3 Muara Ampolu Tapanuli Selatan who were taken from each level of mathematical ability, namely high, medium and low abilities after being given an initial math ability test. To find out the profile of students' spatial reasoning in contextual solving, the research subjects were given a spatial reasoning test. The results showed that students with high and moderate mathematical abilities in solving contextual problems that required spatial reasoning had good results. Meanwhile, low-ability students have difficulty in solving contextual problems so that their spatial reasoning has poor results.